2016
DOI: 10.1007/s12892-016-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of simple sequence repeats associated with quality traits in durum wheat

Abstract: Over recent years, quality has become an important commercial issue for durum wheat breeders. Modern breeding methods are most efficient for producing and supplying the best quality raw materials to the pasta industry. Here we assessed the effectiveness of molecular marker-assisted selection of quality traits in durum wheat. To this end, DNA and quality trait markers were jointly used to analyze quality-related traits in a durum wheat collection. A total of 132 durum wheat (Triticum turgidum ssp. durum) Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…AMOVA revealed highly significant genetic variation among the studied populations, accounting for 12% of the total genetic variance (12.53) (Table 5), which is comparable with previous reports on durum wheat populations in Ethiopia by Mondini et al [28] (18.76%), in Tunisia by Ouaja et al [60] (19%), in the Mediterranean region by Amallah et al [39] (16%), and in India by Arora et al [63] (21.3%). The identified lower proportion of genetic variation among populations than within populations could be explained by the high gene flow between populations, which might have occurred due to the exchange of durum wheat germplasm between farmers and through market systems.…”
Section: Genetic Differentiation Across Populationssupporting
confidence: 89%
See 1 more Smart Citation
“…AMOVA revealed highly significant genetic variation among the studied populations, accounting for 12% of the total genetic variance (12.53) (Table 5), which is comparable with previous reports on durum wheat populations in Ethiopia by Mondini et al [28] (18.76%), in Tunisia by Ouaja et al [60] (19%), in the Mediterranean region by Amallah et al [39] (16%), and in India by Arora et al [63] (21.3%). The identified lower proportion of genetic variation among populations than within populations could be explained by the high gene flow between populations, which might have occurred due to the exchange of durum wheat germplasm between farmers and through market systems.…”
Section: Genetic Differentiation Across Populationssupporting
confidence: 89%
“…Fourteen SSR markers associated with grain quality- and yield-related traits of durum wheat from previous research [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ] were used in this study ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…These precious resources are now mostly conserved in Germplasm Banks. Several studies have found a high variability in the durum Moroccan landraces and claimed that this material should be used in breeding programs for the introgression or improvement of desirable traits [6][7][8]. In particular, landraces could be used to improve, among the others, the grain nutritional and processing quality [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different QTLs for TKW were recently detected on chromosomes 2A, 3B, 4A, 5A, 6A and 7B (Guan et al, 2018;Su et al, 2018;Zhai et al, 2018;Golan et al, 2019;Guan et al, 2019;Sakuma et al, 2019;Wang et al, 2019;Arriagada et al, 2020;Fatiukha et al, 2020;Liu et al, 2020;Mir et al, 2021). The association between different SSR markers and TKW as an indicator for heat tolerance has been also reported in wheat (Ramya et al, 2010;Wang et al, 2012;El-Rawy, 2015;Amallah et al, 2016). In conclusion, enhancing heat tolerance in wheat can be achieved by selecting a higher TKW under heat stress conditions.…”
Section: Bulked-segregant Analysis (Bsa)mentioning
confidence: 59%